Building A Gospel Culture in the Contemporary Church: Ten Imperatives for Church Leaders - Sen Sendjaya (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2022)
As the church finds herself amidst ongoing disruptive changes that are exacerbated by the pandemic, the need for church leaders to reexamine the way the church operates is not merely an important necessity but an urgent priority. The purpose of this article is to outline how church leaders can recalibrate the culture of the church to align with the gospel of Jesus Christ. Drawing on insights from Organizational Leadership and Psychology research, three key features of church culture are discussed in relation to the adaptive challenges that impact the church. As practical implications for church leaders, the article proposes ten leadership imperatives to shape and nurture the gospel culture in the church.